1996
DOI: 10.1002/(sici)1098-2264(199612)17:4<225::aid-gcc4>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Three distinct commonly deleted regions of chromosome arm 16q in human primary and metastatic prostate cancers

Abstract: Human prostate cancers frequently show loss of heterozygosity (LOH) at loci on the long arm of chromosome 16 (16q). In this study, we analyzed prostate cancer specimens from 48 patients (Stage B, 20 cases; Stage C, 10 cases; cancer death, 18 cases) for allelic loss on 16q, using either restriction fragment length polymorphism (RFLP)‐ or polymerase chain reaction (PCR)‐based methods. Allelic losses were observed in 20 (42%) of 48 cases, all of which were informative with at least one locus. Detailed deletion ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(58 citation statements)
references
References 32 publications
4
54
0
Order By: Relevance
“…The region of LOH in 16q23.2-24.1 showed higher frequencies of alteration in distant metastases of breast and prostate cancers (Suzuki et al, 1996;Li et al, 1999). Furthermore, it has been shown by microcell-mediated chromosome transfer that chromosome 16q23-24 is a strong suppressor of the metastatic activity of a prostatic cancer cell line (Mashimo et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…The region of LOH in 16q23.2-24.1 showed higher frequencies of alteration in distant metastases of breast and prostate cancers (Suzuki et al, 1996;Li et al, 1999). Furthermore, it has been shown by microcell-mediated chromosome transfer that chromosome 16q23-24 is a strong suppressor of the metastatic activity of a prostatic cancer cell line (Mashimo et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…[4][5][6] We have investigated several regions of chromosomal loss in prostate cancer using LOH analysis. [7][8][9][10][11][12][13][14][15] CGH is a molecular technique that allows screening of the whole genome for DNA sequence copy number alterations. Regions of increased copy number may contain oncogenes, whereas regions of decreased copy number may contain putative TSGs.…”
Section: Introductionmentioning
confidence: 99%
“…Allelic imbalance at one or more loci was seen in 57 (92%) of the 62 patients. Five patients who did not show AI, three men in the relapse group (24,25,64) and two in the non-relapse group (30, 61) ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…19 Some losses, such as those on 8p and 13q, are associated with early prostate cancer. 11,12,22,23 Others, such as those on 11p and 16q, 15,[20][21][22]24 are more frequent in advanced disease. Several studies have reported an association of AI at certain loci with histopathological features of the RP specimen, including advanced stage, 13,[25][26][27] high Gleason grade 13,26 and perineural invasion.…”
Section: Introductionmentioning
confidence: 99%